Teachers' Perspective of Distance Learning TV in Teaching Speaking During COVID-19 - Qothrunnada Almubarokah; Yudhi Arifani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
The pandemic situation of COVID-19 has damaged various aspects, including education. Distance learning becomes the substitute to facilitate teaching-learning, especially in rural areas. It uses television as a teaching medium to tackle the internet connection problem. Television has been used for a long time and used for entertainment purposes. However, educators start to add educational purposes, especially to learn a language. Unfortunately, television was only an additional teaching tool and was not used thoroughly. This research aims to observe the teacher's perspective of Distance Learning Television (DLTV) to teach speaking, particularly in a rural area, Thailand. The subject research is two English teachers who teach primary school in Thailand, and they use DLTV as the teaching media. The result showed that teachers have a positive perspective on DLTV as a teaching medium, especially in speaking. It contains benefits that can support students in their speaking comprehension. Furthermore, teachers have the role of facilitators and encourage students during the learning process. Despite the drawback of DLTV, it is still be taken care of by teachers by collaborative work with colleagues